Створення «Доктрини Ніксона» та її вплив на зовнішньополітичний курс США наприкінці 60-х – на початку 70-х рр. ХХ ст.] - Колеснікова, Катерина Андріївна; Kolesnikova, Katherine (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проведено аналіз змін у принципах зовнішньої політики, які відбулися з приходом до влади в 1969 р. Річарда Ніксона. Розглянуто зміни у військовій доктрині Америки, переформування сфер національних інтересів, трансформацію засад, на яких формувалися відносини США з іншими країнами світу та ослаблення напруження з СРСР і КНР.In the article was analyzed changes in the principles of foreign policy, which occurred when Richard Nixon came to power in 1969. During the study highlighted the main provisions of which were based on a new concept of foreign policy of the White House. As a result of the study, the author found that Nixon stepped away from the prevailing opinion at that time that only an open confrontation with the communist bloc could lead to the strengthening of America’s position in the international arena. 37th head of the White House was able to objectively analyze the realities of international affairs and in the shortest possible time propose to Washington a new concept of foreign policy, which was able to bring States the status of a single world leader.
Creating «Nixon Doctrine» and its Influence on US Foreign Policy in the Late 60’s – Early 70-ies. of XX Century
Keywords: Ніксон; «Доктрина Ніксона»; зовнішня політика; Америка; Nixon; «Nixon Doctrine»; foreign policy; America